The Behavior of Islamic Educational Organizations: Between Tradition, Modernity and Spirituality - Endiana, Yeni; Nasith, Ali (El-Idare: Jurnal Manajemen Pendidikan Islam, 2026)
Rapid social transformation in the modern era poses new challenges for Islamic educational organizations. Islamic education is required to preserve its religious identity while simultaneously adapting to contemporary developments. The need to integrate tradition, modernity, and spirituality renders the study of organizational behavior in Islamic education both conceptually and practically significant. This study aims to critically examine the characteristics, the roles of tradition, modernity, and spirituality, as well as the ideal model of organizational behavior in Islamic educational institutions. The research employs a qualitative method using a library research approach to analyze relevant theoretical frameworks and empirical findings. The results indicate that: (1) the characteristics of organizational behavior in Islamic education include work motivation as an act of worship, the implementation of an Islamic organizational culture, adherence to the principle of maslahah (public benefit), and the perception of leadership as a trust (amanah); (2) tradition plays a crucial role in shaping organizational identity and maintaining value stability, modernity drives transformation and innovation, while spirituality provides meaning and direction for organizational practices; and (3) consequently, the ideal model of organizational behavior in Islamic education is one that is rooted in traditional values, adaptive to contemporary changes, and oriented toward spiritual principles. his study is expected to contribute to the advancement of scholarly discourse on organizational behavior in Islamic education, particularly in integrating tradition, modernity, and spirituality as a foundational framework for developing adaptive and value-based Islamic organizational cultures.